Tinjauan Kriminologis Tindak Pidana Terhadap Putusan Perkara Kejahatan Pembunuhan Berencana Dalam Perspektif Hukum Islam (Studi Kasus Terhadap Putusan Perkara No.523/Pid.B/2017/PN.PLP) - Mustaming, Mustaming; Juniar, Mita (Datuk Sulaiman Law Review (DaLRev), 2020)
AbstractCriminological review of the case decision No.523 / Pid.B / 2017 / PN.PLP,an overview leads to the Identity of the Defendant and the scene described in the contents of the accused's indictment, as well as knowing the plot or storyline of the Defendant when committing a murder crime. Islamic criminal law review of the case decision No.523 / Pid.B / 2017 / PN. PLP in Islamic criminal law includes premeditated murder and persecution itself. The actions of the defendant are included in the main punishment was qishash, takzir and diat. If the victim or the victim's family / heir forgives, the defendant must pay a diyat in the form of compensation. Diyat or compensation for its value is left up to the ulil amri decision or the judge. Meanwhile, the defendant can also get an acquittal as long as he gets forgiveness from the victim's family. Thus according to Islamic criminal law, premeditated murder which result in serious injury by the defendant received qishash, takzir and diat laws.Â AbstrakTinjauan kriminologis terhadap putusan perkara No.523/Pid.B/2017/ PN.PLP, suatu tinjauan yang mengarah kepada Identitas si Terdakwa dan tempat kejadian yang dipaparkan pada isi dakwaan Terdakwa, serta mengetahui alur atau jalan cerita Terdakwa pada saat melakukan suatu kejahatan pembunuhan. Tinjauan hukum pidana Islam terhadap putusan perkara No.523/Pid.B/2017/PN. PLP dalam hukum pidana Islam termasuk pembunuhan berencana dan penganiyaan itu sendiri perbuatan terdakwa masuk dalam hukuman pokoknya adalah qishash, takzir dan diat. Apabila korban atau keluarga korban/ahli waris memaafkan maka terdakwa harus membayar diyat berupa ganti rugi. Diyat atau ganti rugi nilainya diserahkan kepada keputusan ulil amri atau hakim. Sedangkan bisa juga hukuman bebas untuk terdakwa asalkan mendapatkan pemaafan dari keluarga korban. Dengan demikian menurut hukum pidana Islam tentang pembunuhan berencana yang mengakibatkan luka berat oleh terdakwa tersebut mendapatkan hukum qishash, takzir dan diat.